A Review: The Effect of Plant Growth Regulators on Micropropagation of Aglaonema sp. - Zahara, Meutia; Win, Cho Cho (Yayasan Pertanian Tropika Indonesia (YPTI), 2020)
Nowadays, Aglaonema sp. becomes very famous in Indonesia. especially during the pandemic covid-19. Many people tend to stay home to stop the spreading of the virus. One of the activities that can be done during staying home is growing the plants as well as ornamental plants. Aglaonema sp. is one of the important and well-known foliage ornamental plants in Indonesia, commonly called â€œSri Rezekiâ€. The generative or sexual reproduction of Aglaonema sp. is difficult, and it contains some endogenous pathogen. The common propagation techniques are by cutting and seed, which risky in the spreading of the pathogen. Micropropagation is an advanced technique to produce a large number of plants in a short time and pathogen-free transplant. This manuscript endeavor to include some important investigations and studies on the use of the Plant Growth Regulators (PGRs) on the Aglaonema sp. micropropagation.